Differentiating mammary carcinoma from ovarian and endometrial carcinoma using GATA3, MAM, and PAX8 expression: validations and limitations. Issue 1 (July 2016) - Shash, Lobna S.; Shakweer, Marwa M.; Abou Gabal, Hoda H.
Abstract : Background: Breast, ovarian, and endometrial cancers commonly share many morphologic and immunophenotypic features. Breast cancer may first present by means of metastasis. It can be associated with second primaries, commonly gynecological cancers. Distinguishing breast carcinomas from these tumors when the setting is questionable for double primaries versus metastasizing disease is challenging and must be investigated using tissue-specific markers. Aim: The aim of this study was to validate the diagnostic utility of GATA3, MAM, and PAX8 expression in differentiating breast cancer from endometrial and ovarian cancer. Materials and methods: Immunohistochemical studies were conducted using GATA3, MAM, and PAX8 for 18 primary ovarian carcinomas, 19 primary endometrial carcinomas, and 58 primary mammary carcinomas. Additional 11 cases of metastatic tumors of established breast and ovarian origin were tested for these markers as a small sample test. Results: Diagnostic accuracy for GATA3 expression in breast carcinomas was 97.8% as compared with 74.7% for MAM expression, which was observed in all tested categories whether of breast or gynecological origin. PAX8 expression revealed 100% specificity for gynecological cancers and 92.1% diagnostic accuracy. Conclusion: Immunohistochemical expression of GATA3 and PAX8 can be used as diagnostic markers in differentiating breast carcinomas from endometrial and ovarian carcinomas. However, MAM is strongly unadvisable as a breast tissue marker when ovarian or endometrial carcinomas are in question.